Distributed CPS-based model predictive compensator for DC microgrids with cyber-layer constraints. (December 2022) - Dong, Xiao-Gang; Ge, Ming-Feng; Liu, Zhi-Wei; Ai, Xiaomeng
Abstract: In this paper, we design a distributed model predictive compensator (DMPC) in the cyber layer based on the mechanism of rolling optimization to compensate the bias of the nominal voltage in the droop control. We then present the structure of cyber–physical system (CPS) to combine the DMPC with the droop control in the physical layer to form a uniform framework as well as accomplish high-quality voltage regulation and power allocation. We also deal with the case of the cyber-layer constraints since the states of cyber-layer among the distributed generators (DGs) of the microgrid are generally constrained due to their great impacts on the stability of the physical layer. Especially, the presented CPS-based DMPC is developed in a fully distributed manner, namely, only the compensated parameters of the neighbors can be accessible for each DG and no global information is employed in the whole control process. Besides, the stability of the presented DMPC can be guaranteed if the initial communication states satisfy the consistency constraint. The effectiveness and feasibility of the presented CPS-based DMPC is verified numerically in the presence of the motor faulty. It is demonstrated from the theoretical analysis and simulation results that the settling time for compensating the droop parameter is acceptable and satisfies the principle of "plug-and-play". Highlights: A distributed model predictive compensator (DMPC) based on the framework of the cyber physical system (CPS) is proposed. The proposed algorithm considers the state constraints of cyber layer in solving the control problem of DC microgrid. It is the first attempt to design the DMPC at the cyber layer such that the inherent constraints of the communication states can be guaranteed. Both the problems of voltage deviation adjustment and power distribution for the DC microgrid can be simultaneously solved by using the presented algorithm.